Strong and Weak Hypotheses - Chiffi, Daniele; De Florio, Ciro (Logic and Logical Philosophy, 2025)
I In this paper, we investigate the nature of empirical hypotheses used in scientific reasoning and the act of formulating hypotheses. This is achieved through a novel logical framework in which we provide specific semantics for two types of hypotheses: a strong and a weak sense of hypothesis, each characterized by different logical structures. This framework enables us to better characterize certain aspects of hypothetical reasoning in scientific practice, especially when we attempt to rationally deny the content of an empirical hypothesis.